INTERTEXTUALITY THEME AND NARRATIVE TRANSFORMATION ON VERONICA ROTH’S DIVERGENT - Misla Geubrina; Mayasari; Aditya Anggada; Nurul Aini (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2026)
This study investigates the intertextuality in Veronica Roth's Divergent by examining the thematic and narrative relationships between the novel and earlier dystopian literary works. Grounded in Julia Kristeva's theory of intertextuality and Gérard Genette's concept of transtextuality, the research explores how Divergent absorbs, transforms, and reconstructs established dystopian conventions to generate new meanings within contemporary young adult fiction. Employing a qualitative descriptive design and library research approach, the study uses Divergent as the primary source of data, while books and scholarly publications on intertextuality, dystopian literature, and literary criticism serve as secondary sources. Data were collected through close reading, textual documentation, and thematic coding, and analyzed using qualitative textual analysis focusing on thematic intertextuality and hypertextual narrative transformation.The findings reveal that Divergent establishes significant intertextual relationships with canonical dystopian novels, particularly Nineteen Eighty-Four, Brave New World, The Giver, and The Hunger Games. These relationships are evident in the reconstruction of major dystopian themes, including identity, social conformity, freedom, resistance, fear, knowledge, and social classification. However, Veronica Roth does not merely replicate these earlier texts; instead, she transforms their ideological and narrative structures to address contemporary concerns regarding diversity, individuality, ethical responsibility, and personal agency. From Genette's perspective, Divergent functions as a hypertext that creatively adapts the dystopian tradition by modifying the protagonist's developmental journey, institutional power structures, conflict patterns, and representations of authority. The concept of "Divergence" itself serves as a symbolic reinterpretation of identity that challenges rigid systems of categorization and promotes the coexistence of multiple human qualities.The study concludes that intertextuality in Divergent functions as a creative strategy for literary innovation rather than simple textual borrowing. By engaging in dialogue with earlier dystopian narratives, Roth constructs a novel that simultaneously preserves the conventions of the dystopian genre and redefines them for twenty-first-century readers. This research contributes to contemporary literary criticism by demonstrating how intertextuality enriches the thematic complexity and narrative originality of young adult dystopian fiction while expanding scholarly discussions beyond feminist, ideological, and sociological approaches that have dominated previous studies of Divergent.